The effect of cervical pessary on increasing gestational age at delivery in twin pregnancies with asymptomatic short cervix: a systematic review and meta-analysis of randomized controlled trialsAJOG Global Reports at a Glance - Amir Hossein Norooznezhad, MD; Nikan Zargarzadeh, MD; Ali Javinani, MD; Seyedeh Maedeh Nabavian, MD; Shohra Qaderi, MD; Shayan Mostafaei, MD; Vincenzo Berghella, MD; Yinka Oyelese, MD; Alireza A. Shamshirsaz, MD, FACOG (Elsevier, 2024)
Objective: The incidence of preterm delivery is much higher in twin pregnancies than in singletons and even higher if a short cervical length is detected in the second trimester. Studies are contradictory regarding the efficacy of a cervical pessary to decrease preterm birth in twin pregnancies and short cervical length. To conduct a systematic review and meta-analysis investigating the efficacy of cervical pessary in prolonging gestation, preventing preterm birth, and reducing adverse neonatal outcomes in twin pregnancies with an asymptomatic short cervix. Data sources: PubMed, Scopus, Web of Science, and ClinicalTrials.org were searched for randomized controlled trials from inception to June 2023. Study eligibility criteria: In this study, randomized controlled trials comparing the cervical pessary to expectant management in the pregnant population with twin gestations and asymptomatic short cervix were included. Methods: The Cochrane risk-of-bias-2 tool for randomized controlled trials was used for the evaluation of the risk of bias in included studies. A meta-analysis was performed by calculating risk ratio and mean difference with their 95% confidence interval using the random effects model or fixed effect model on the basis of heterogeneity and accounting for potential covariates among the included randomized controlled trials. Results: A total of 6 randomized controlled trials were included in the analysis. Cervical pessary did not significantly increase the gestational age at delivery in twin pregnancies with asymptomatic patients (mean difference, 0.36 weeks [−0.27 to 0.99]; P=.270; I2=72.0%). Moreover, the cervical pessary use did not result in a reduction of spontaneous or all-preterm birth before 37 weeks of gestation (risk ratio, 0.88 [0.77-1.00]; P=.061; I2=0.0%). There was no statistically significant difference in the composite neonatal adverse outcomes (risk ratio, 1.001 [0.86-1.16]; P=.981; I2=20.9%), including early respiratory morbidity, intraventricular hemorrhage, necrotizing enterocolitis, and confirmed sepsis. Conclusion: The use of cervical pessary in twin pregnancies with asymptomatic short cervix does not seem to be effective in increasing the gestational age at delivery, preventing preterm birth, or reducing adverse neonatal outcomes. This indicates that alternative interventions should be sought for the management of this patient population.